Diagnostic riddle– case report of ocular syphilis - Marta Bociąga-Kożuch; Aleksandra Raczyńska; Dorota Trela; Aleksander Garlicki; Tomasz Berus (Journal of Ophthalmic Inflammation and Infection)
Abstract Syphilis is one of sexually transmitted infections (STIs). The incidence of Treponema pallidum infection has increased in the last 20 years. This rise is also evident in ophthalmological practice, with cases of ocular syphilis becoming more frequent. We present a case of a 29-year-old patient with blurred vision in his left eye. Patient showed no general symptoms, nor previous history of eye disorders. On ophthalmological examination, the best-corrected visual acuity (BCVA) was 20/20 in the right eye (OD) and 20/80 in the left eye (OS). The left eye presented high intraocular pressure (IOP) of 31 mmHg and symptoms of anterior uveitis with a linear branching corneal erosion. A B-scan ultrasound of the left eye revealed no vitritis. The preliminary diagnosis of herpetic infection was made, and antiviral therapy was introduced. Despite the initial improvement, symptoms of active anterior uveitis were found on follow-up visits. After approximately 4 weeks of ambulatory treatment, the patient was admitted to the hospital because of roseolae and lumps of the left iris, which appeared accompanied by a rash on patients’ lower limbs. Laboratory tests confirmed syphilis and human immunodeficiency virus (HIV) coinfection. During hospitalization intravenous treatment with penicillin and antiretroviral drugs was introduced. Therapy with penicillin was continued to 21 days with improvement in examination. On a follow-up visit after 6 months BCVA in both eyes was 20/20. It is crucial to consider testing for STIs, especially Treponema pallidum infection, in the diagnostic process of patients with nontypical or nonresponsive to treatment ocular symptoms.